2015
DOI: 10.1007/s11422-015-9692-6
|View full text |Cite
|
Sign up to set email alerts
|

Encountering science education’s capacity to affect and be affected

Abstract: What might science education learn from the recent affective turn in the humanities and social sciences? Framed as a response to Michalinos Zembylas's article, this essay draws from selected theorizing in affect theory, science education and science and technology studies, in pursuit of diverse and productive ways to talk of affect within science education. These discussions are framed by desires to transcend traditional epistemic boundaries and practices. The article concludes offering some associated ambigui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…that social issues are value-laden and therefore invoke emotions in individuals, often related to students' own experiences and beliefs (cf. Sandahl, 2015aSandahl, , 2019Barton, 2009;Alsop, 2016). In line with Endacott and Brooks (2013, p. 44;cf.…”
Section: Theoretical Framework: Academic Social Perspective Takingsupporting
confidence: 58%
“…that social issues are value-laden and therefore invoke emotions in individuals, often related to students' own experiences and beliefs (cf. Sandahl, 2015aSandahl, , 2019Barton, 2009;Alsop, 2016). In line with Endacott and Brooks (2013, p. 44;cf.…”
Section: Theoretical Framework: Academic Social Perspective Takingsupporting
confidence: 58%
“…Since it has been concluded that all three specific factors do come into play in the general construct, it is suggested that practitioners emphasise all three in the educational setting in order to affect students and consequently develop their interest as well as cognitive skills. The importance of including affective dimensions in science education has been argued and researched in recent years (Alsop, 2016;Rahayu, 2015;Zembylas, 2016). Attitude towards biotechnology may be especially pertinent to work with for practitioners because the many inherently affective and behavioural topics in modern biotechnology do separate the area from other areas of science.…”
Section: Discussionmentioning
confidence: 99%
“…With findings in neuroscience supporting a highly integrated model of emotion and cognition (Damasio, 1997;LeBlanc, McConnell, & Monteiro, 2015), however, as well as a turn toward the affective in other academic disciplines (Alsop, 2016;Zembylas, 2016), the role of emotions in science learning is becoming not only more acceptable, but is increasingly recognized as an area ripe for, and in urgent need of, deep examination (Alsop, 2016;Fortus, 2014;Hadzigeorgiou & Schulz, 2014;Zembylas, 2016). The limited studies that do exist regarding the role of emotions in science education have primarily focused on three overlapping areas of impact on learning: emotions toward science as a discipline, emotions in science class, and emotions within the doing of authentic science (Jaber & Hammer, 2016).…”
Section: The Role Of Emotions In Science Education and Connections Tomentioning
confidence: 99%